2018
DOI: 10.2174/0929866524666171026125300
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Two Stress-Inducible tau Class Glutathione Transferases from Glycine max Revealed Significant Catalytic and Structural Diversification

Abstract: Our results suggest that GmGSTU5-5 and GmGSTU8-8 display different or overlapping substrate specificities and kinetic properties. The biological role of GmGSTU5-5 and GmGSTU8-8 may be relevant to the detoxification of toxic compounds or the binding of bioactive metabolites that function in cell regulation and stress defence mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The 3-D models of all these eight CmGSTs chiefly contain α helix, β sheet, turn, and random coil ( Figure 6 ). The helices observed in the C-terminal domain contribute to the formation of the H-site and, therefore, to the xenobiotic substrate specificity ( Pouliou et al, 2017 ). Intriguingly, the C-terminal domain was composed mainly of α helices, and the N-terminal domain was composed of α helices and β sheets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3-D models of all these eight CmGSTs chiefly contain α helix, β sheet, turn, and random coil ( Figure 6 ). The helices observed in the C-terminal domain contribute to the formation of the H-site and, therefore, to the xenobiotic substrate specificity ( Pouliou et al, 2017 ). Intriguingly, the C-terminal domain was composed mainly of α helices, and the N-terminal domain was composed of α helices and β sheets.…”
Section: Resultsmentioning
confidence: 99%
“…In rice, 79 GST genes were identified, and many of the GST genes were commonly regulated during various abiotic (20), arsenate (32), and biotic stress (48) conditions (Jain et al, 2010). Pouliou et al (2017) find that GmGSTU5-5 and GmGSTU8-8 exhibited high activities as glutathione peroxidases, capable of reducing toxic hydroperoxides in Glycine max. Wang et al (2019) report that 14 of 330 TaGST genes could respond to different abiotic stresses and hormones, especially salt stress and abscisic acid in wheat.…”
Section: Identification Of Hami Melon Gstsmentioning
confidence: 94%
“…Amino acid sequence alignments and phylogenetic analysis of PvGm GSTUG with the tau class GSTs from G. max and P. vulgaris revealed that the PvGm GSTUG displayed higher identity with the Pv GSTU2-2 and Gm GSTU8-8 isoenzymes and, from the evolutionary point of view, formed a separate clade (Figure 5 ). Although the accurate prediction of the parent sequences was impossible, we can nevertheless speculate that most of the PvGm GSTUG sequence was derived from Pv GSTU2-2 (Chronopoulou et al, 2012a ) and Gm GSTU8-8 (Pouliou et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of recombinant CdGSTM1-1 was performed according to the general protocol described in published procedures [19][20][21][22]. E. coli BL21 (DE3) cells harboring recombinant plasmid (pET-3aCdGSTM1-1) were grown at 37 • C in 1 L LB medium containing ampicillin (100 µg/mL).…”
Section: Expression and Purificationmentioning
confidence: 99%
“…The thermal stability of CdGSTM1-1 was also investigated using differential scanning fluorimetry (DSF) on an Applied Biosystems ® real-time PCR StepOne™ instrument, as described by Pouliou et al [19]. Fluorescence monitoring was carried out at 4-99 • C at a rate of 1 • C/min.…”
Section: Thermal Stabilitymentioning
confidence: 99%